nIFTY galaxy cluster simulations – III. The similarity and diversity of galaxies and subhaloes - Elahi, Pascal J.; Knebe, Alexander; Pearce, Frazer R.; Power, Chris; Yepes, Gustavo; Cui, Weiguang; Cunnama, Daniel; Kay, Scott T.; Sembolini, Federico; Beck, Alexander M.; Davé, Romeel; February, Sean; et al. (Oxford University Press, 2016)
We examine subhaloes and galaxies residing in a simulated Λ cold dark matter galaxy cluster (Mcrit200=1.1×1015h−1M⊙) produced by hydrodynamical codes ranging from classic smooth particle hydrodynamics (SPH), newer SPH codes, adaptive and moving mesh codes. These codes use subgrid models to capture galaxy formation physics. We compare how well these codes reproduce the same subhaloes/galaxies in gravity-only, non-radiative hydrodynamics and full feedback physics runs by looking at the overall subhalo/galaxy distribution and on an individual object basis. We find that the subhalo population is reproduced to within ≲10 per cent for both dark matter only and non-radiative runs, with individual objects showing code-to-code scatter of ≲0.1 dex, although the gas in non-radiative simulations shows significant scatter. Including feedback physics significantly increases the diversity. Subhalo mass and Vmax distributions vary by ≈20 per cent. The galaxy populations also show striking code-to-code variations. Although the Tully–Fisher relation is similar in almost all codes, the number of galaxies with 109 h− 1 M⊙ ≲ M* ≲ 1012 h− 1 M⊙ can differ by a factor of 4. Individual galaxies show code-to-code scatter of ∼0.5 dex in stellar mass. Moreover, systematic differences exist, with some codes producing galaxies 70 per cent smaller than others. The diversity partially arises from the inclusion/absence of active galactic nucleus feedback. Our results combined with our companion papers demonstrate that subgrid physics is not just subject to fine-tuning, but the complexity of building galaxies in all environments remains a challenge. We argue that even basic galaxy properties, such as stellar mass to halo mass, should be treated with errors bars of ∼0.2–0.4 dex.